The Issue of Teachers’ Professional Competence and Pedagogical Competence in English Teaching- Learning Process - Marthisa Olivia Billik (Universitas PGRI Madiun, 2020)
The existence of development in the education field requires teachers to be able to act more than just a teacher who knows how to teach. To become an advanced teacher, a teacher should have good professional competence and pedagogical competence. However, there are still problems that hinder the teacher when conducted the teaching and learning process. The problems that appear in the English classroom are teachers’ professional competence and teachers’ pedagogical competence. This study aims to describe and explain teachers’ experience in dealing with their professional and pedagogical competence in teaching the English language. This is a qualitative study and used interview and observation as the instruments to collect the data from 3 teachers as the participant in SMA NegeriBenlutuSo’e - East Nusa Tenggara. The results of the study found that teachers’ low professional and pedagogical competence caused the teachers to have inadequate English teaching competence in teaching. It caused the teachers to teach the students with inappropriate learning materials, monotonous learning activities, and uncooperative assessment methods. The results of this study also recommend that teachers have high English language proficiency and teaching competence to be able to teach English in Senior High School.